Enterococci as a key parameter for water quality index: Purires River, Costa Rica - Chacón Jiménez, Luz María (2018)
This study used the Canadian Water Quality Index (CWI) to characterize water sampled at three points within the Purires River micro basin, Costa Rica. The first sampling point is located in a high zone with domestic agricultural activities, the second point around the mid-point of the flow of the river, and the third point at the lowest zone with extensive agricultural activities mainly centered on the production of fresh vegetables. Eleven physicochemical parameters (As, Cd, Cr, biochemical oxygen demand (BOD), chemical oxygen demand (COD), NH4+, NO3−, Pb, pH, percent saturation of dissolved oxygen (PSO), and total suspended solids (TSS)) and two microbiological parameters (fecal coliforms and enterococci) were evaluated. We evaluated three different Canadian Water Quality Indexes (CWIs): CWI-1 included only physicochemical parameters, CWI-2 included CWI-1 parameters plus fecal coliforms, and CWI-3 included CWI-2 in addition to enterococci. Statistical analysis of individual parameters showed significant differences between sampling sites. CWI-1 was unable to discriminate between the three sampling points, and characterized the water quality as ‘fair’. CWI-2 was only able to discriminate when the water contained high levels of chemical and microbiological contaminants, while CWI-3 adequately discriminated water quality at each of the sampling points. The evaluation of enterococci together with more traditional water quality parameters enabled better categorization of surface water quality.